Analysis of slope characteristics in the Al-Hasin river basin and their impact on the spatial distribution of land use patterns - صالح, نادين; ياسر المحمد; جولييت سلوم (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The characteristics of slopes determine the features of prevailing geomorphological processes and their implications on practical aspects of human life, represented by land uses. This emphasizes the significant importance of studying slopes when establishing any projects in order to achieve their success requirements and investment potential. By analyzing the characteristics of slopes in the Al-Hasin River basin, including elevation degree, slope gradient, and slope aspect, it is evident that the basin's surface gradually rises from sea level in the west to 1100m in the east, and from 400m in the south to 700m in the north. Additionally, slopes with above-average grades dominate 40.00% of the basin's area, and southward slope direction prevails over 18.36% of the total basin area. The main land use patterns have been identified, revealing that agricultural land is the primary land use pattern in the study area, covering 62.52% of the basin's total area, followed by forests and urban areas at 28.11% and 9.28%, respectively. Subsequently, the results of the slope characteristics categories were matched with the spatial distribution of land use patterns to highlight the relationship between them, demonstrating the impact of slope characteristics on the expansion and contraction of land use patterns.